Trade integration and business cycle synchronization in East Asia - Kwanho Shin; Yunjong Wang (Osaka University, Institute of Social and Economic Research (ISER), 2003)
As trade integration deepens in East Asia, it is expected that there will be closer links in business cycles among East Asian countries. Theoretically, however, increased trade can lead business cycles across trading partners to shift in either direction: while inter-industry trade resulting in higher specialization would induce less synchronization, intra-industry trade could overturn this tendency. By using the data for twelve Asian economies, this paper finds that intra-industry trade is the major channel through which business cycles become synchronized among Asian economies, although increased trade itself does not necessarily lead to close business cycle coherence. This result has important implications for the prospects of a currency union in the region.
Keywords: E32; F36; F41; 330; Regionale Wirtschaftsintegration; Konjunkturzusammenhang; Intraindustrieller Handel; Währungsunion; Ostasien